Penggunaan Software Pembelajaran Matematika Untuk Meningkatkan Minat Belajar Siswa Kelas XI IPA SMA Negeri 1 Marga - Ni Wayan Dian Permana Dewi (FPMIPA IKIP PGRI Bali, 2018)
This study aims to determine whether the use of mathematics learning software can increase the students' interest of learning in class XI IPA SMA 1 Marga. Data collection method used in this research is using questionnaire of student learning interest, which consist of very low, low, high and very high category. The results of the initial analysis of students as many as 24 people, showed a very low interest in learning. Furthermore, after classroom action research was conducted, using mathematics learning software in the form of Autograph and Microsoft Mathematics make the interest in learning, increase for the students. Cycle 1 takes linear inequality system material yields interest with high category of 66, 67%, very high category equal to 20, 83%. While cycle 2 take the material of building space generate interest with high category equal to 70, 83% and very high category 29,17%. The conclusion obtained from this research is the use of mathematics learning software able to increase student's interest in class XI IPA SMA Negeri 1 Marga.